The Nonisothermal Elastohydrodynamic Problem for a Journal Bearing - Albagachiev, A. Yu; Usov, P. P. (Journal of machinery manufacture and reliability, 2024)
The nonisothermal elastohydrodynamic problem for an oil film journal bearing is considered. The mathematical bearing model is presented. A method for joint numerical solution of nonisothermal lubrication equations and contact deformation equations is presented. The results of numerical calculations are compared with known experimental data on the minimum thickness of the lubricating layer and the maximum temperature in the lubricating layer.